Mental practice as a novel learning strategy for donning and doffing personal protective equipment during the COVID-19 pandemic. Issue 5 (September 2020) - Riggs, Jamie; McGowan, Melissa; Petrosoniak, Andrew; Hicks, Christopher
ABSTRACT: The coronavirus disease 2019 (COVID-19) pandemic presents challenges to the effective use of personal protective equipment, including equipment shortages, staff unfamiliarity, and physical distancing. Mental practice has been used as an alternative learning strategy in medicine for the development of technical skills. We developed educational materials with the aim of using mental practice to overcome these challenges and increase provider skill and confidence with the use of personal protective equipment. A mental practice script integrating cognitive, kinesthetic, and visual cues with a list of procedural steps was created and iteratively refined. To allow the use of this tool by providers unfamiliar with the principles of mental practice, accompanying explanatory materials were created and disseminated widely through the Free Open Access Medical education (FOAMed) community. By creating easily accessible resources to facilitate effective mental practice, providers may be able to increase their skill and comfort with the procedure while conserving personal protective equipment and respecting physical distancing guidelines.